STUDY ON FOOD AND FEEDING BIOLOGY OF TRICHOGASTER FASCIATA BLOCH & SCHNEIDER, 1801 FROM A WETLAND OF NADIA DISTRICT OF WEST BENGAL - KHONGNGAIN1, OLDALIN; Das, Sudhir Kumar; Bhakta, Dibakar (Journal of the Inland Fisheries Society of India, 2021)
Study on relative length of gut, food and feeding habit, gastrosomatic index and hepatosomatic index of Trichogaster fasciata were carried out from a wetland of Nadia district, West Bengal. A total 462 specimens of 27 to 89 mm size were collected for a period of one year (April 2003 to March 2004). The size at first maturity was recorded at 60 mm and the fishes were categorized into two groups, size group-I (< 60 mm) and size group-II ( 60 mm) for easy interpretation. The relative length of the gut (RLG) for the size group-I varied from 3.156 to 5.525 with mean value as 4.483Â±0.37 and in size group-II from 4.955 to 5.907 with mean value as 5.647Â±0.31. The food items observed in the guts were algae, diatoms, zooplankton, insects and mosquito larvae, decayed organic matter etc. Algae were the most dominant groups of food for both the groups with 23.0% and 25% followed by decayed organic matter with 20.6 % and 25.1% in group I and in group II, respectively. The common algae observed in the gut content were Spirogyra sp., Ulothrix sp., Chlorococum sp., Oscillatoria sp., Tribonema sp., Cymbella sp., Pinnularia sp. and Navicula sp. The highest percentage of algae (28.02%) was found in the month of February and that of zooplankton (9.99%) during the month of June. The value of the Gastrosomatic index (GaSI) for male varied from 0.104 to 4.955 and female 0.261 to 5.655. The HSI for male & female ranged from 0.669 to 1.351 & 0.808 to 1.397 respectively. Key words: Trichogaster fasciata, food and feeding habit, RLG, GaSI, wetland, Nadia district.